Analysis of Conventional and Hybrid Parallel Adder Circuits - Naik, Sampoorn; Ramesh, K. B. (Journal of Electronic Design Engineering, 2022)
In electronic circuits, there are three factors that need to be considered while designing any circuit and they are device speed, power and area distribution. Most computational systems require parallel adders which greatly affect speed, there are different kinds of adders which are great in one or more aspects. Hence there is a need for hybridization and continuous improvement of existing adders.in this review /research paper let’s explore various kinds of basic adders such as carry save adder (CSA), carry skip adder (CKSA), carry look ahead adder (CLA), Carry select adder (CSA) and carry increment adder (CIA) and to also look into the advantages of new and improved designs in certain new adders which include CIA_CLA Carry Save Adder There is also a theoretical design of a proposed adder included in this paper